1983
DOI: 10.1103/physrevlett.50.2086
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Phenomena below Melting of the One-Component Two-Dimensional Plasma

Abstract: This Letter reports investigations by molecular dynamics of the melting transition of a two-dimensional one-component plasma consisting of 511 particles with logarithmic interactions confined to a disk. Evidence is presented for a weak first-order transition occurring at T^ = ^V^r^ with r^ ^ 142 and with a melting entropy =^0.17 K. This small entropy is attributed to important premelting phenomena which are cooperative, cyclic permutations of six and more particles as revealed by labeling experiments.PACS numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 3 publications
4
28
0
Order By: Relevance
“…Qualitative evidence for such heterogeneity has been apparent since the earliest simulations of melting in hard discs by Alder et al 50,51 where large-scale cooperative particle motion was found to be a conspicuous feature of the melting process. This type of permutational particle motion was also noticed long ago in the simulated melting of one-component plasmas 52 and measurements on granular fluid, 53 colloidal fluid, 54,55 and dusty plasma [56][57][58] melting in near two dimensions. Quite recently there have been molecular dynamics studies of collective atomic motion associated with superheating of three dimensional crystals of Lennard-Jones particles 59,60 where many aspects of dynamics heterogeneity in GF liquids are exhibited such as a strong growth of the non-Gaussian parameter, clusters of mobile particles, cooperative particle motion, etc.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Qualitative evidence for such heterogeneity has been apparent since the earliest simulations of melting in hard discs by Alder et al 50,51 where large-scale cooperative particle motion was found to be a conspicuous feature of the melting process. This type of permutational particle motion was also noticed long ago in the simulated melting of one-component plasmas 52 and measurements on granular fluid, 53 colloidal fluid, 54,55 and dusty plasma [56][57][58] melting in near two dimensions. Quite recently there have been molecular dynamics studies of collective atomic motion associated with superheating of three dimensional crystals of Lennard-Jones particles 59,60 where many aspects of dynamics heterogeneity in GF liquids are exhibited such as a strong growth of the non-Gaussian parameter, clusters of mobile particles, cooperative particle motion, etc.…”
Section: Introductionsupporting
confidence: 69%
“…55 This type of particle permutation motion has also been observed in particle tracking measurements of melting in quasi-two dimensional lattices of colloidal particles, 54,[96][97][98] quasi-two dimensional driven granular fluids 53 and simulations of the melting of quasi-two dimensional plasma crystals. 13,52,56 It is thus not surprising that we see prevalent string-like collective motion in our simulations of melting in Ni crystals. What is somewhat surprising is that the size distribution and geometrical form of the excitations is so similar in geometrical form to GF liquids.…”
Section: Cooperative Atomic Motion In Bulk Meltingmentioning
confidence: 69%
“…Monte Carlo simulations show that large, three-dimensional (3D) clouds of ions form solid-phase crystals at Γ≈172–178 (see ref. 1 and references therein) and at Γ≈140 for two-dimensional (2D) systems2. In these crystals, the inter-ion distance is typically of the order of 10 μm, set by the strength of the applied trapping fields.…”
mentioning
confidence: 99%
“…In the Landau-Lifshitz formalism, excitations are coherent over the magnetic exchange length (27), which is -8 nm in Fe at low temperatures. Similar dynamical correlations, characteristic of DCDs, are found in a variety of physical systems (28).…”
mentioning
confidence: 99%